The Relationship Between Self-Confidence and Kayaking Results Extracurriculars at SMPN 1 Ciampel - Irvan Ariyanto; Rahmat Iqbal; Evi Susanti (UNIVERSITAS NEGERI MAKASSAR, 2024)
In research, This researcher has the goal you want to achieve which is To prove the relationship of trust in self with results rowing like an extracurricular at SMPN 1 Ciampel. Study This uses a descriptive quantitative technique with a correlation that is used to test measurement kayaking and measurement levels, such as self-athlete kayaking. On research This population used is participant extracurricular rowing at SMPN 1 Ciampel, totalling 120 students. Population in study This amounts to more than 100, then by the opinion of the sample in study This is 20%-25% or more from a population that is as many as 40 students / I extracurricular rowing at SMPN 1 Ciampel. Instruments used Kayaking Results Instrument and Self-Confidence Instrument. From the results of research that has been done, then can conclude that there is a connection very strong positive between Trust in self with the results of rowing like a student at SMP Negeri 1 Ciampel with a mark coefficient correlation of 0.952, with thereby said that the more high level of trust self For Participate in extracurricular training Paddle then the Kayaking Results will also be the more Good.